2020
DOI: 10.21467/ajgr.8.1.1-7
|View full text |Cite
|
Sign up to set email alerts
|

Proximate, Phytochemical and Antioxidant Mineral Compositions of Four Different Brands of Tea

Abstract: The comparative studies of the proximate, phytochemical and antioxidant mineral compositions of four different brands of green tea were investigated. The four different brands, Tianshi®, Qualitea®, Slimfit®, and Xiang® were purchased from a supermarket in Ihiala Local Government Area of Anambra State, Nigeria. The samples were pulverized and stored in an airtight container prior to analysis. The proximate composition was analysed using AOAC method while phytochemical compositions of the green teas were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The concentration of PAHs in all dumpsites during rainy and dry seasons, indicates that high molecular weight (HMWPAHs) Chrysene, Benzo(b)fluoranthene, Benzo (k) fluoranthene, Indeno(1,2,3cd) pyrene, Diabenez(a,h)anthracene which are highly toxic and cancerous are more in dumpsite located around the residential arears during rainy season while they are predominant in Market dumpsites during dry season. The predominance of HMWPAHs at all the dumpsites in this study also agrees with the work of Ifemeje [5], on Ibadan municipal dumpsites.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The concentration of PAHs in all dumpsites during rainy and dry seasons, indicates that high molecular weight (HMWPAHs) Chrysene, Benzo(b)fluoranthene, Benzo (k) fluoranthene, Indeno(1,2,3cd) pyrene, Diabenez(a,h)anthracene which are highly toxic and cancerous are more in dumpsite located around the residential arears during rainy season while they are predominant in Market dumpsites during dry season. The predominance of HMWPAHs at all the dumpsites in this study also agrees with the work of Ifemeje [5], on Ibadan municipal dumpsites.…”
Section: Discussionsupporting
confidence: 92%
“…Ifemeje [5] studied distribution of polycyclic aromatic hydrocarbons (PAHs) in soils from Onitsha municipal active and dormant solid waste dumpsites. The study showed that Low molecular weight PAHs were not detected in both active and dormant dumpsite.…”
Section:  Conclusionmentioning
confidence: 99%
“…Furthermore, acid and alkali treatments showed an increase in the alkaloid content by 5.90 and 6.56%, respectively, while microwave treatments exhibited no effect on alkaloid content. The concentration of alkaloids in edible plants is generally nontoxic because boiling or steaming reduces their levels in plant extracts . Hydrothermal treatments such as blanching and autoclaving result in a higher reduction of antinutrients owing to the water-soluble nature of the minerals as they are leached to the cooking medium .…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of alkaloids in edible plants is generally nontoxic because boiling or steaming reduces their levels in plant extracts. 45 Hydrothermal treatments such as blanching and autoclaving result in a higher reduction of antinutrients owing to the water-soluble nature of the minerals as they are leached to the cooking medium. 12 Furthermore, during various thermal and hydrothermal treatments, antinutrients such as phytates form insoluble complexes with proteins and minerals, which may also be responsible for lower levels.…”
Section: Acs Foodmentioning
confidence: 99%
“…These components act synergistically to ensure a desired beneficial effect (Raederstorff et al, 2003). Tea are rich in proteins, carbohydrates, minerals and trace elements, lipids, vitamins, carotenoids, flavonoids and volatile compounds (Graham, 1992;Belitz and Grosch, 1997;Ifemeje et al, 2020). However, most of the tea brands used in this study do not contain sugars, fat, fiber or sodium, with considerable amount of energy and low proteins in their nutritional information.…”
Section: Discussionmentioning
confidence: 97%